Controlling locomotion during the acceleration phase in sprinting and long jumping - Glize, D.; Laurent, M. (Journal of Sports Sciences, 1997)
The production of a stabilized locomotor pattern is crucial in sporting activities such as the run-up in long jumping, a task which is characterized by high spatio-temporal constraints. The aims of this study were as follows. First, we wished to investigate how athletes stabilize their stride patterns so as to strike the take-off board accurately. Previous studies have argued that during the initial accelerative phase of the run-up, athletes attempt to produce a stereotyped stride pattern. We investigated this initial phase in more detail by examining the kinematic parameters of long jumpers' strides and their spatial consequences. These data were then compared with the stride patterns observed in a sprinting task, which did not impose the same spatio-temporal constraints. Our second aim was to compare the stride patterns of skilled and unskilled jumpers.Kinematic stride parameters were measured in two ways. The temporal parameters (flight time, stance time) were recorded by a microcomputer attached to the athlete, whereas the spatial parameters (stride length) were measured directly from the footprints the subjects made on the track. The results confirmed those of previous studies, showing that long jumpers initiate locomotor adjustments in the last 3-4 strides before take-off, but a more detailed analysis revealed that long jumping is characterized by adjustments during the first few strides. These adjustments were not seen in the sprinting task, where systematic variations of accumulated error were observed. These stride adjustments differed from those seen in previous studies and thus permit a more comprehensive understanding of the control involved in the tasks studied. The patterns exhibited by the skilled and unskilled subjects were very similar overall, but differed in that variations in accumulated error were less marked for the skilled subjects, who tended to make early stride adjustments sooner than the unskilled subjects. These results are discussed in relation to the cognitive and ecological approaches to movement coordination.